Pengembangan Tools untuk Mengatasi Kepadatan Pasien di Instalasi Gawat Darurat - Kusumawardhani Kusumawardhani; Hanny Handiyani; Nurdiana Nurdiana (Journal of Telenursing (JOTING), 2021)
This study aims to develop tools in solving the problem of service flow and patient density in the ER and develop solutions to solve them. The method used is the analysis of results and implementation gaps using a literature review. Problems were analyzed using fishbone and solved using PDCA tools. The data were analyzed descriptively by looking at the frequency distribution of staff perceptions regarding the density of patients in the ER. The results showed that 98% of the staff said the activation of the ER full of crowds was 1x in one shift, 46.9% said the response time after the full ER system was activated was more than 6 hours, 64% said the time required for patients in the emergency room to get an outpatient Hospitalization is around 24-72 hours and 85.7% said the use of the crowded emergency room system was not optimal in overcoming the density of patients in the emergency room. In conclusion, the management in overcoming the problem of overcrowded ER by nurse managers is not optimal in terms of follow-up after the system is activated. The involvement of nurse managers in the inpatient department is needed in the problem of patient density in the ER. Keywords: Management Function, Overcrowded Emergency Room, Nurse Manager